Enactment of corporate laws for building legal environment and their effectiveness - Hamzah, . (Opción, 2019)
This study investigates the current legal environment of Indonesia in the light of new enactment of laws and effectiveness of their enforcement. The SPSS software was used to carry out regression analysis. The findings show a positive relationship between legal environment and legal effectiveness, however the enactment of new laws was found to be unrelated and insignificant due to significant uncertainties and past legacy still present in the Indonesian law. In conclusion, it is time for creating public awareness to understand what corporate activities could be harmful to them.